Implementation of homogeneous and heterogeneous tidal arrays in the Inner Sound of the Pentland Firth - Patel, MD; Smyth, ASM; Angeloudis, A; Adcock, TAA (Springer, 2024)
The effective development of tidal stream energy sites requires an understanding of constraints limiting extraction of the resource. This study considers the implications of certain spatial constraints on the practical tidal stream energy resource. Specifically, we investigate how bathymetry influences array design and how much energy is obtained when heterogeneous arrays (comprising of turbine devices with varying specifications) are deployed at a site compared to homogeneous arrays. A novel framework for designing arrays of homogeneous and heterogeneous turbine specifications is set out and applied to the Inner Sound of the Pentland Firth as a case study. The array that delivers the most energy yield consists of 5 m diameter turbines with homogeneous diameter and control. However, this case achieves the lowest capacity factor due to the assignment of a homogeneous rated speed across the entire site, which does not account for the spatial variability of the resource. A 6% increase in capacity factor is achieved when turbines of heterogeneous control (rated speed = 1.5–2.5 m/s) are deployed across the site, producing a similar amount of power. The power per turbine can be increased if a heterogeneous diameter and control array design is adopted because 69% fewer turbines can be deployed with only a 5% decrease in average power. Heterogeneous array design maximises usage of a site, whilst allowing the maximum allowable diameter of turbine to be deployed in areas, and to exploit the spatial variation of the resource across a site by tailoring turbines to operate at appropriate rated speeds.